Characterization of HuH6, Hep3B, HepG2 and HLE liver cancer cell lines by WNT/Î² - catenin pathway, microRNA expression and protein expression profile - Di masi, A.; Viganotti, M.; Antoccia, A.; Magrelli, A.; Salvatore, M.; Azzalin, G.; Tosto, F.; Lorenzetti, S.; Maranghi, F.; Mantovani, A.; Macino, G.; Tanzarella, C.; et al. (Cellular and Molecular Biology, 2010)
Somatic mutations in the genes members of WNT/Î²-catenin pathway, especially in CTNNB1 codifying for Î²-catenin, have been found to play an important role in hepatocarcinogenesis. The purpose of this work is to characterize alterations of the WNT/Î²-catenin signalling pathway, and to study the expression pattern of a panel of microRNAs and proteins potentially involved in the pathogenesis of liver cancer. In this respect, the molecular characterization of the most used liver cancer cell lines HuH6, Hep3B, HepG2, and HLE, could represent a useful tool to identify novel molecular markers for hepatic tumour. A significant modulation of FZD7, NLK, RHOU, SOX17, TCF7L2, TLE1, SLC9A3R1 and WNT10A transcripts was observed in all the four liver cancer cell lines. The analysis of selected microRNAs showed that miR-122a, miR-125a and miR-150 could be suitable candidates to discriminate tumoural versus normal human primary hepatocytes. Finally, Grb-2 protein expression resulted to be increased more than two-fold in liver cancer cell lines in comparison to normal human primary hepatocytes. These advances in the knowledge of molecular mechanisms involved in the pathogenesis of liver cancer may provide new potential biomarkers and molecular targets for the diagnosis and therapy.